PENGARUH CAPITAL, ASSET QUALITY, MANAGEMENT, EARNING, LIQUIDITY TERHADAP PERTUMBUHAN LABA (Study Empiris Pada Bank Umum Swasta Nasional Yang Tercatat Di Bursa Efek Indonesia) - Widia Putri Ramadini; Roni Malavia Mardani; Budi Wahono (UNIVERSITAS ISLAM MALANG, 2018)
ABSTRACT The purpose of this study was to determine the effect and provide evidence empirically, variables of capital, assets, management earnings, and liquidity have significant effect towards banking profit growth. This research is a survey research using secondary data, namely the annual financial statements of banking companies that are registered on BE I. Sample banks used in the study include all banks going public on the IDX period 2007-2008. The type of data used is secondary data. The data source is the ratio banking finance listed on the IDX. Documentation and data collection methods literature review. Data analysis method uses classical assumption test, multiple linear regression, test , F test and coefficient of determination. The results of the study show that partially banking profit growth is stated in the ratio of financial ratio consisting of variable capital adequacy ratio Keywords: Capital, Assets, Management, Earnings, Liquidity And Profit Growth